Comparison between the influence of Syntocinoo and Metergine on the Postpartum hemorrhage and the sideeffect of Metergine - F Ramezanzadeh; F Vasegh Rahim parvar; Z Monjamed; M Mahmoodi (Tehran University of Medical Sciences, 1999)
The objectives of this research are determine the difference in the effect of "Syntocinon" and "Syntocinon and Methergine" on postpartum blood loss as well as the side effects arising from administration of methergine.The number of subjects, under study was 108. The subjects were divided into two grups of 54. All subjects received an intramuscular injection of 10 units of Syntocinon after delivery of baby, while one group received, in addition, an intramuscular injection of 0.2 mg. of Methergine, after delivery of placenta. Then the amount of hemorrhage within 24 hours after delivery, determined by Higham's pictorial chart, the postpartum hemorrhage (P.P.H.) determined visually and experimentally, the difference of hemoglobin and hematocrit measured before and 24 hours after delivery, in two groups were compared. The statistical tests showd no significant difference between any of the particulars of the subjects in the two groups.As shown by the results, that the average hemorrhage in "Syntocinon" group was 145.56 ml. Meanwhile, there were three cases of postpartum hemorrhage (5.6%) in this group. The average hemorrhage in "Syntocinon and Methergine "group was 130 ml. wih two cases of postpartum hemorrhage (3.7%). The statistical tests showed no significant difference between average hemorrhage and cases of postpartum hemorrhage (p = 0.5, df=l) in both groups. These findings were objectively confirmed by the comparison between hemoglobin and hematocrit before and 24 hours after delivery in both groups, suggesting no significant difference between the two groups as regards, pre-and post delivery hemoglobin and hematocrit differences.The findings also suggest that there is no significant difference between the groups as regards the incidence of nausea, vomiting, chest pain, dyspnea, headache, mild and severe after-birth pains, backache, Systolic blood pressure of 140 (mmHg) and higher as well as diastolic blood pressure of 90 (mmHg) and higher. However, There have always been significant differences between the average systolic and diastolic blood pressures as measured 6,15,30 and 45 minutes as well 1, 2, 3 and 4 hours after delivery of placenta, as compared to pre delivery ones (p<0.05).